Genetically predicted circulating levels of cytokines and the risk of oral cavity and pharyngeal cancer: a bidirectional mendelian-randomization study - Wu, Kehan; Sun, Qianhui; Liu, Dongxu; Lu, Jiayi; Wen, Deyu; Zang, Xiyan; Gao, Li (Frontiers in Genetics, 2024)
Background Epidemiological research has established associations between various inflammatory cytokines and the occurrence of oral cancer and oropharyngeal cancer (OCPC). We performed a Mendelian randomization (MR) analysis to systematically investigate the causal relationship between inflammatory cytokines and OCPC Methods We performed a bidirectional two-sample MR analysis using OCPC from 12 studies (6034 cases and 6585 controls) and genome-wide association study (GWAS) results for 41 serum cytokines from 8,293 Finns, respectively. Inverse variance weighting was used as the primary MR method and four additional MR methods (MR Egger, Weighted median, Simple mode, Weighted mode) were used to examine genetic associations between inflammatory traits and OCPC, and Cochran's Q test, MR-Egger intercept, leave-one-out analysis, funnel plot, and multivariate MR (MVMR) analysis were used to assess the MR results. Results The results suggested a potential association between high gene expression of Macrophage inflammatory protein-1α (MIP1α/CCL3) and an increased risk of OCPC (Odds Ratio (OR): 1.71, 95% Confidence Interval (CI): 1.09-2.68, p = 0.019). Increasing the expression levels of the interleukin-7 (IL-7) gene by 1 standard deviation reduced the risk of OCPC (OR: 0.64, 95%CI: 0.48-0.86, p = 0.003). In addition, multivariate Mendelian randomization analysis also showed the same results (MIP1α/CCL3, OR：1.002，95% CI：0.919-1.092，p = 0.044; IL-7, OR：0.997，95% CI：0.994-0.999，p = 0.011). Conversely, there was a positive correlation between genetic susceptibility to OCPC and an increase in Interleukin-4 (IL-4) (OR: 1.04, 95%CI: 1.00-1.08, p = 0.027). Conclusion Our study systematically assessed the association between inflammatory cytokines and the risk of OCPC. We identified two upstream regulatory factors (IL-7 and CCL3) and one downstream effector factor (IL-4) that were associated with OCPC, offering potential avenues for the development of novel treatments.